A microstructure-based modeling approach to assess aging-sensitive mechanics of human intervertebral disc. (March 2021) - Kandil, Karim; Zaïri, Fahmi; Messager, Tanguy; Zaïri, Fahed
Highlights: Novel modeling approach to predict age effects on intervertebral disc mechanics. Age-related changes in the disc rigidity, radial and axial transversal responses. Regional dependence on the age-related alteration in microstructure-mechanics. Age-related alteration in lamellar/inter-lamellar interaction. Abstract: Background and objective: The human body soft tissues are hierarchic structures interacting in a complex manner with the surrounding biochemical environment. The loss of soft tissues functionality with age leads to more vulnerability regarding to the external mechanical loadings and increases the risk of injuries. As a main example of the human body soft tissues, the intervertebral disc mechanical response evolution with age is explored. Although the age-dependence of the intervertebral disc microstructure is a well-known feature, no noticeable age effect on the disc stiffness is evidenced in the in-vitro experimental studies of the literature. So, if the disc intrinsic mechanics remains constant, how to explain the correlation of disc degeneration and disc functionality loss with age. Methods: A microstructure-based modeling approach was developed to assess in-silico the aging-sensitive mechanics of human intervertebral disc. The model considers the relationship between stress/volumetric macro-response and microstructure along with effective age effects acting at the lamellar and multi-lamellar scales. The stress-stretch and transversal responses of the different disc regions were computed for various age groups (13-18, 36, 58, 69 and 82 years old) and their evolution with age was studied. Results: While matching with in-vitro experimental data, the predicted stiffness was found to increase while passing from adolescent young discs to mature older discs and then to remain almost constant for the rest of life. Important age-related changes in the disc transversal behavior were also predicted affecting the flexibility of the disc, changing its volumetric behavior, and modifying its dimensions. Conclusion: The developed approach was found able to bring new conclusions about age-dependent mechanical properties including regional dependency. The disc mechanics in terms of rigidity, radial and axial transversal responses were found to alter going from adolescent to middle age where the disc reaches a certain maturity. After reaching maturity, the mechanical properties undergo very slight changes until becoming almost constant with age.